Étude caryologique de quelques ophrys - Shimoya, C; Ferlan, L (Revista Ceres, 1956)
In the metaphase I of the meiotic division of microspores were found the following haploid sets: Ophrys tenthredinifera Willd. n =19, seldom n = 18; O. bombylifiora Link n=18; O. Speculum Link n = 18 and seldom n = 17. Consequently, in the Algiers zone, Ophrys tenthredinifera populations are represented by an hypersomic race with n =18 + 1.